Impact of space weather on ionospheric dynamics in Bangladesh: Insights from 2022–2023 TEC analysis - Mostofa, Sadia; Ahmmed, Mohammad Badal; Hasan, Mohammad Mahdi; Some, Jagobandhu; Sharif, Muhammad (Journal of Bangladesh Academy of Sciences, 2025)
Our study, which investigates the impact of space weather on ionospheric variability over Bangladesh, a region near the Equatorial Ionization Anomaly (EIA), using Total Electron Content (TEC) measurements derived from Global Positioning System (GPS) observations, is of significant importance. The analysis, covering 2022 and 2023, characterized by heightened solar activity, reveals a pronounced spatial gradient in TEC values, primarily modulated by proximity to the EIA and geomagnetic disturbances. Seasonal and diurnal patterns further highlight the influence of solar radiation and geomagnetic activity on ionospheric behavior. Notably, severe geomagnetic storms in March and September 2022 and in March and April 2023 induced substantial TEC perturbations, amplifying ionospheric variability. These findings provide critical insights into the complex interactions between solar -terrestrial processes and geomagnetic dynamics, with significant implications for navigation, communication systems, and space weather forecasting in low-latitude regions such as Bangladesh. J. Bangladesh Acad. Sci. 49(1); 103-111: June 2025